The relationship between running distance and coaches` perception of team performance in professional soccer player during multiple seasons - Ponce-Bordón, J. C.; García-Calvo, T.; Candela-Guardiola, J. M.; Serpiello, F. R.; López del Campo, R.; Resta, R.; Pulido, J. J. (Scientific Reports, 2022)
This study analyzed how the physical movement profile of soccer matches evolved throughout a season by assessing the variability of different metrics depending on the season phase. In addition, the evolution of running distances was investigated in the relation to the team performance based on the coaches` perception. Games from four consecutives Spanish LaLiga seasons (n = 1520) were recorded using an optical tracking system (i.e., ChyronHego). Total distance (TD), distance covered between 14 and 21 km h-1 (MIRD), 21-24 km h-1 (HIRD), and > 24 km h-1 (VHIRD) were analyzed, as well as the number of efforts between 21 and 24 km h-1 (Sp21) and > 24 km h-1 (Sp24). Seasons were divided into four phases (P): P1 (matches 1-10), P2 (11-19), P3 (20-29), and P4 (30-38). Linear mixed models revealed that soccer players covered significantly greater distances and completed a higher number of sprints in P2 and P3. Also, team performance evaluated by soccer coaches was positively related to TD, HIRD, VHIRD and Sp21 in P1. A negative relationship was observed between team performance and distance covered at speeds below 21 km h-1 in P2 and P3. Team performance was negatively related to TD, MIRD, and HIRD, and Sp21 in P4. As conclusion, the team performance perceived by coaches is related to the movement profile throughout a season, and it significantly influences the evolution of soccer players` movement profiles. Specifically, it seems that the players of the best teams have the best physical performance at the beginning of the season with respect to the rest of the phases.